The effect of the Coriolis coupling on H plus ND reaction: A time dependent wave packet study - Akpinar, Sinan; Hekim, Seda Surucu (Elsevier Science Bv, 2013)
We present a quantum scattering calculation of initial-state-resolved reaction probabilities, integral cross section, initial state selected reaction rate constants and thermal rate constant for exchange and depletion channels of the H+ND reaction. The calculations are carried out using Coriolis coupling (CC) method on the modified NH2(A) over tilde (2)A(1) potential energy surface(PES). The initial state selected reaction probabilities are calculated for 0.0-0.5 eV of collision energy range. The reaction probabilities for depletion channel shows some sharp and large resonances associated with long-lived collision complexes, as compared to exchange channel. Integral cross sections for both reactions depend strongly on initial rotational states. The calculated thermal reaction rate constant for the depletion channel is in a good agreement with the values previously obtained by the centrifugal sudden approximation, experimental and semiclassical results. (C) 2013 The Authors. Published by Elsevier B. V. All rights reserved.
Keywords: Angular-Momentum J-Greater-Than-0; Quantum-Mechanical Calculations; Scattering Calculations; Dynamics; H+O-2